Perlindungan Hukum Terhadap Konsumen Atas Produk Pangan Kemasan Yang Tidak Memiliki Label - Nurdin, Ningsi; Akyuwen, Rory Jeff; Labetubun, Muchtar Anshary Hamid (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The expiry date of a food and beverage product in the form of the date, month and year of storage of the food and beverage product is printed on the packaging label which is intended to inform consumers about the product consumed. Includes expiration dates that are useful to consumers, retailers, sellers and manufacturers. Adding expiration dates to food gives consumers clear information about product safety, allows traders and sellers to manage inventory of traded products, and allows manufacturers to know the product warranty period after it has been produced.Purposes of the Research: The purpose of writing carried out by the author is to find out the effect of consumer buying interest on packaged food products that do not have labels and to know and explain how consumers protect packaged food products that do not have labels.Methods of the Research: The research method used by the author in this study is normative juridical where research is carried out to obtain data through library studies, namely various literature and scientific materials, brochures and so on.Results of the Research: The results of the study indicate that packaging can influence consumer interest in buying. If we look at it now, it's not only the large food industry products that are starting to intensively create attractive packaging innovations, this has also begun to be followed by MSME business actors or home industries. Labels help consumers to obtain product information for the benefit and welfare of consumers. With this packaged information, it will reduce the losses that consumers get. The benefit of including the correct label or information on the package is to provide knowledge to the parties concerned with the item. With this article to protect consumers, in order to balance the potential awareness that is built in the relationship between business actors and consumers. And to improve the quality and quality of merchandise properly